Variabilidad genética del cerdo Congo Santandereano mediante marcadores microsatélite (2023)
The Congo pig is a zoogenetic resource characteristic of the Santander Department in Colombia. Its genetic diversity was evaluated using 12 different microsatellites, from 37 blood samples. DNA was extracted using Corpogen 2000 kit®; the microsatellites were amplified using PCR (Polymerase Chain Reaction) and electrophoresis of vertical chamber for typification. Using software (Genetix®) the observed heterozygosity (Ho) and expected heterozygosity (He), the number of alleles for each locus, the allelic frequency and the FIS statistics were calculated. The polymorphic indices (PIC) were calculated using the microsatellite excel Toolkit. The twelve microsatellites employed were polymorphic, a total of 52 alleles were detected, with a median of 4.3 alleles. The (He) range interval values was 0.42 (minimal markers S009 and SW240) – 0.76 (Maximal marker CGA1). The medium Ho was 35%, the majority of the markers were useful with polymorphism information content (PIC) superior to 0.5. The inbreeding index (FIS 0.5) reveals a high deficit of heterozygotes. This finding strongly suggests a low genetic variability of the Santander Congo pig, suggests a possible trend of increase in consanguinity, possibly related to a reduced population size. © 2017, Universidad de Cordoba,Servicio de Publicaciones. All rights reserved.